AN INTRODUCTION TO TIME COMPLEXITY AND NP-COMPLETE - Yadav, Upender; Verma, Vikash; Saha, Parmod (IJRDO -Journal of Computer Science Engineering, 2015)
The time complexity of an algorithm is the amount of computer time required by an algorithm to run to completion. Computational time complexity analyzes of evolutionary algorithms (EAs) have been performed since the mid-nineties. The ﬁrst results were related to very simple algorithms, such as the (1+1)-EA, on toy problems. The objective of this paper is to review the time complexity knowledge seen in research work devoted on synthesis, optimization, and effectiveness of various sorting algorithms. We will examine different sorting algorithms in the lines and try to discover the tradeoffs between them